INFLUENCE OF BUDGET EFFICACY ON HOUSEHOLD EFFECTS IN KENYA - Munyua, Cyrus M (Machakos University, 2019)
The purpose of this study is to find out whether Budget Efficacy influences household effects under Fiscally Decentralized economy as it is today in Kenya. The study was anchored on the theory of fiscal federalism and Agency Theory and adopted a positivist research philosophy in determining the research strategy and method of this strategy. A Census involving the 47 county governments was conducted based on population size, nature of the county i.e rural or urban set up and size of the annual budget support from the national government. The Study adopted the Survey and Evaluation Program (NASSEP V) frame that the Kenya Bureau of Statistics currently operates to conduct household-based surveys to also conduct a household survey in the county governments on household effects in Kenya. The study employed an inductive ex post facto cross sectional quantitative survey design. Secondary panel data was collected from County Treasuries while Primary data was collected through household surveys and Fiscal and Monetary Departments of county assemblies. Data for the period 2015-2017was used to run an univariate and multiple regressions using STATA software. Both descriptive and inferential statistics were generated and provided results for interpretation. The study established a significant association between budget efficacy and household effects. The findings of this study are expected to empower citizens through access of information on the real meaning and effects of fiscal asymmetric decentralization while policy makers will know the strength of the correlation between fiscal asymmetry and household effect in order to match monetary policy with the needs of lower government levels for implementation of the country’s financial framework.
Keywords: NASSEP V; Budget Efficacy; Household Effects; Positivist Philosophy; Fiscal; Policy; Actual Expenditure